EVALUASI PROGRAM GURU PENGGERAK DI KECAMATAN CIKARANG PUSAT KABUPATEN BEKASI - Yeni, Nofri; Muthi, Ibnu; Sugiarti, Diyah Yuli (Jurnal Riset Guru Indonesia, 2023)
This research aims to determine the effectiveness of the movement teacher program and to assess the program in terms of context, input, process, and product in Cikarang Pusat District, Bekasi Regency, which has been implemented. This research uses an evaluative approach with a descriptive method, and data collection is conducted qualitatively. Qualitative research is aimed at understanding the phenomenon of what is experienced by the research subjects. The results of this research indicate that the Context Evaluation has mostly met the criteria required for implementing the program. Meanwhile, the Input Evaluation shows that most of the criteria have been met in the implementation of the Movement Teacher Program. Based on the data previously presented regarding the implementation of the program process evaluation, the Movement Teacher Program has fulfilled the requirements. The Product Evaluation concludes that this program has had a significant positive impact on education in the region. There has been an improvement in student achievement and the development of teacher skills.